Examining the Relationship Between Resilience, Mental Health and Fitness Outcomes in Firefighters - Daniel R. Greene; A. Maleah Holland-Winkler; Austin A. Kohler; William R. Kinnaird (Journal of Functional Morphology and Kinesiology, 2025)
Background: Firefighters have an increased risk of both mental and physical health conditions due to experiencing various forms of extreme stress regularly. High levels of resiliency may help firefighters overcome stressful situations and promote better mental and physical health. Objectives: The primary aim of the present study was to examine the relationship between resilience and other psychological variables. The secondary aim was to determine the relationship between psychological variables and firefighter fitness outcomes. Methods: Participants included 79 full-time male firefighters with a mean age of 35.9. They completed the following psychological questionnaires in this order: PTSD checklist for DSM-5, Dispositional Resilience Scale 15-item, State–Trait Anxiety Inventory for Adults and Beck Depression Inventory. They completed the following fitness tests in this order: maximum number of push-ups in two minutes, maximum time holding a plank and minimum time completing running and/or walking 1.5 miles. Results: Resilience was correlated with and predicted significant variance in depression, trait anxiety, state anxiety and PTSD symptoms in firefighters (all p’s < 0.025). Further, all psychological variables were significantly correlated with and predictive of each other. However, only scores on the Beck Depression Inventory were associated with push-ups completed (p = 0.014). No other psychological variable was related to fitness outcomes in firefighters. Conclusions: This study demonstrated resilience was significantly related to anxiety, depressive symptoms and PSTD symptoms in firefighters but not fitness outcomes. This highlights the protective effects of resilience on mental health, but future work needs to explore other psychological mechanisms to predict physiological performance variables in firefighters.